Factors associated with suicide risk among nurses and physicians: a cross-section study - Fernanda de Oliveira Freire; Samira Reschetti Marcon; Mariano Martínez Espinosa; Hugo Gedeon Barros dos Santos; Moisés Kogien; Nathalie Vilma Pollo de Lima; Jesiele Spindler Faria (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objective: to estimate the prevalence and factors associated with suicide risk among nurses and physicians. Method: a cross-sectional study carried out at a university hospital with 216 health professionals, who answered a socio-demographic-labor questionnaire, the Mini International Neuropsychiatric Interview (MINI) for assessing suicide risk, and the Depression, Anxiety and Stress Scale (DASS 21). The Poisson Regression Model was used for multiple analysis. Results: it was identified that variables such as not having a partner, history of attempted suicide, stress and depression symptoms were statistically associated with suicide risk. The prevalence of lifelong suicide attempts among nurses was 9.41%, and among physicians, 2.29%. Conclusion: the findings of this investigation enable the understanding of suicidal behavior among hospital nurses and physicians, in addition to enabling the development of prevention strategies in order to reduce suicide risk prevalence in this population group.